2020
DOI: 10.1088/1755-1315/478/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

The Acrosome Integrity Examination of Post-thawed Spermatozoa of Several Ongole Grade Bull in Indonesia Using Giemsa Staining Method

Abstract: Cement cryopreservation is a preserving technique of spermatozoa cells that the spermatozoa cells can be used in a long period of time. Frozen semen is produced by the National Artificial Insemination Center (AIC) and the Regional Artificial Insemination Center (RAIC) in Indonesia. The indicators in predicting spermatozoa fertilizing ability include individual motility and movement scores, but the indicators have not been able to accurately predict the spermatozoa fertilizing ability, Acrosome integrity of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Individual variations of Bali cattle caused significant differences in the intact acrosome cap values of AD, PT1, and PT2 groups (p < 0.05, Table 3). Before freezing, Bali cattle's average intact acrosome cap was 91.06% (Damayanti et al, 2021), while frozen semen was 64.12 ± 1.21-76.82 ± 1.55% (Prihantoko et al, 2020). The best percentage of intact acrosome cap in the PT1 group was for Individual E, with a value of 74.04%, but it was not different from individual J with a value of 73.89%.…”
Section: Plasma Membrane and Intact Acrosomementioning
confidence: 90%
See 2 more Smart Citations
“…Individual variations of Bali cattle caused significant differences in the intact acrosome cap values of AD, PT1, and PT2 groups (p < 0.05, Table 3). Before freezing, Bali cattle's average intact acrosome cap was 91.06% (Damayanti et al, 2021), while frozen semen was 64.12 ± 1.21-76.82 ± 1.55% (Prihantoko et al, 2020). The best percentage of intact acrosome cap in the PT1 group was for Individual E, with a value of 74.04%, but it was not different from individual J with a value of 73.89%.…”
Section: Plasma Membrane and Intact Acrosomementioning
confidence: 90%
“…The stained slide was washed with distilled water and observed using a microscope (Olympus CX23, Japan -Optilab advanced V2, Indonesia) by counting 200 spermatozoa. Acrosomes of intact sperm were indicated by the purple top of the head, while those with light color imply deterioration (Chowdhury et al, 2014;Prihantoko et al, 2020).…”
Section: Observation Of Semen Deteriorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though eosin-nigrosin (EN) staining brings reliable results when identifying fresh semen quality, two studies [ 17 , 18 ] found this technique inappropriate when evaluating post-thaw spermatozoa. On the contrary, Trypan-blue/Giemsa (TBG) staining belongs to bright-field staining techniques with good credibility when analyzing the acrosomal damage in cryopreserved spermatozoa [ 19 ]. The acrosome intactness test (AIT) introduced by Gopalkrishnan et al [ 20 ] belongs to simple but tedious tests based on the halo effect of intact acrosomes in samples diluted with PBS and glucose solution smeared on gelatin-coated slides.…”
Section: Markers Of Structural Integritymentioning
confidence: 99%
“…Cryopreservation is a technique that allows for the preservation of biological samples at extremely low temperatures, which slows down the metabolic activities of the cells, thereby ensuring their preservation for more extended periods (Davis et al., 1963). This technique brought a breakthrough revolution in assisted reproduction and is indispensable for livestock (Prihantoko et al., 2020). Although hypothermic conditions during cryopreservation enable the long‐term storage of biological samples, ultra‐low temperatures lead to irreversible mechanical damage at the cell level (Khan & Ijaz, 2008).…”
Section: Introductionmentioning
confidence: 99%